A comparative study of ferric carboxy maltose versus iron sucrose for iron deficiency anaemia in pregnancy - James, Nikitha; Antartani, Ramalingappa C.; James, Neha Anu (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Anaemia is a major contributor to maternal morbidity and mortality worldwide. Ferric carboxy maltose is a novel iron preparation which can treat anaemia faster and more effectively. Thus, this study aimed to evaluate the efficacy and safety of FCM in pregnancy and also to compare the same with Iron sucrose in pregnancy. Methods: This was a Prospective, Hospital based, Comparative study performed on 120 women who attended the department of obstetrics and gynaecology at KIMS, Hubli for a duration of one and a half years (2017-18). The patients received either FCM or Iron sucrose, with 60 participants in each group. Results: Among 120 subjects, 75% of the patients had microcytic, hypochromic anaemia, 1.4% had dimorphic anaemia.38.33% of patients had moderate anaemia (Hb 6-7.9g/dl). After FCM infusion, rise in Hb at 2 weeks was 1.5g/dl and at 4 weeks was 2.9 g/dl. Serum ferritin levels raised by 36.7 and 63.1 mcg/l at 2 and 4 weeks with FCM respectively. On comparison with Iron sucrose, the Hb rise was statistically better with FCM at 4 weeks, whereas the ferritin levels were significantly improved with FCM at both 2 and 4 weeks after treatment. Side effects in mild form occurred in 7.5% of the subjects. Conclusions: FCM is a safe, effective alternative to other parenteral iron therapies, offering faster correction of anaemia and iron replenishment. Its use in pregnancy will significantly reduce the burden of maternal mortality and morbidity.